Goodnight, Butterfly - Burach, Ross (New York : Scholastic Press, 2022)
Butterfly wakes up while Porcupine is having breakfast, and Porcupine tries to explain what it means to be nocturnal and Butterfly considers the advantages of a nighttime life while trying to get back to sleep.
Companion to: The very impatient caterpillar.
K-3
1.7
Keywords: Butterflies -- Juvenile fiction; Porcupines -- Juvenile fiction; Nocturnal animals -- Juvenile fiction; Sleep -- Juvenile fiction; Humorous stories; Butterflies -- Fiction; Porcupines -- Fiction; Nocturnal animals -- Fiction; Sleep -- Fiction; Animal fiction; Humorous fiction